2017
DOI: 10.1093/toxsci/kfx241
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Induces Members of the mmu-miR-466-669 Cluster Which Reduces NeuroD1 Expression

Abstract: Chronic arsenic exposure can result in adverse development effects including decreased intellectual function, reduced birth weight, and altered locomotor activity. Previous in vitro studies have shown that arsenic inhibits stem cell differentiation. MicroRNAs (miRNAs) are small noncoding RNAs that regulate multiple cellular processes including embryonic development and cell differentiation. The purpose of this study was to examine whether altered miRNA expression was a mechanism by which arsenic inhibited cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…The expression of several early neural markers was also investigated. Previous studies focusing on acute arsenic exposure have shown a reduction in Ascl1 , a transcription factor needed for neural differentiation (Liu & Bain, 2014, 2018). Whereas Ascl1 mRNA expression was reduced at an acute 0.5‐μM arsenic exposure, it was not altered at the lower 0.1‐μM level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of several early neural markers was also investigated. Previous studies focusing on acute arsenic exposure have shown a reduction in Ascl1 , a transcription factor needed for neural differentiation (Liu & Bain, 2014, 2018). Whereas Ascl1 mRNA expression was reduced at an acute 0.5‐μM arsenic exposure, it was not altered at the lower 0.1‐μM level.…”
Section: Discussionmentioning
confidence: 99%
“…PCR efficiency and linearity were determined using a standard curve generated by serial dilutions of five concentration points (10 −3 to 10 −7 ng DNA) of the gene of interest. The geometric mean of Gapdh and β2-microglobulin was used for normalization, as the expression of these reference genes does not vary due to arsenic exposure (Liu & Bain, 2018). Relative fold expression was compared with the Week 0 controls and quantified by the delta-delta Ct method (Schmittgen & Livak, 2008).…”
Section: Gene Expression Analysis Using Quantitative Pcrmentioning
confidence: 99%
“…C2MC, also known as miR-297-669 cluster, is derived from intron 10 of the Polycomb group gene sex comb on the midleg with four MBT domains-2 (Sfmbt2) on mouse chromosome 2 [16]. MiRNA members of this cluster have been shown to be upregulated upon different harmful stimuli such as nutrient depletion conditions in Chinese hamster ovary (CHO) cells [17,18], acetaminophen-induced liver injury [19] and liver aging in mice [20], sodium arsenite exposure in P19 mouse embryonal carcinoma cells [21] and in the ischemic cortex 24 h after transient middle cerebral artery occlusion (tMCAo) in rats [22].…”
Section: Introductionmentioning
confidence: 99%